Analisis Faktor Risiko Cemaran Mikroba pada Depot Air Minum Isi Ulang di Kota Makassar - Kasim, Khiki Purnawati; Haerani, Haerani; Budirman, Budirman; Stientje, Stientje (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Refillable drinking water (AMIU) is a practical solution for the people of Makassar City in meeting their daily drinking water needs. However, its microbiological quality is often questioned due to contamination of Escherichia coli (E. coli) and Coliform. Studies show that 45% of refillable drinking water depots (DAMIUs) in Makassar are contaminated with E. coli, which has the potential to cause gastrointestinal diseases. Examination data from the Health Office has identified DAMIU that is positive for contamination, while risk factors such as hygiene and sanitation, treatment methods, and handling practices by operators have not been widely studied. This study aims to identify contaminated DAMIU and analyze risk factors for microbial contamination to formulate recommendations for improvement. The research design used a cross-sectional method with two stages, namely analysis of secondary data from the Health Office's examination results to map E. coli positive DAMIU, as well as field surveys through hygiene-sanitation observation and operator interviews. The analysis was carried out quantitatively using the Microbial Risk Assessment (MRA) approach. The results showed 7 E. coli positive DAMIU with levels of 4–30 CFU/100 ml. The Probability of Illness (Pill) value ranges from 2.8 × 10⁻¹ to 3.5 × 10⁻¹, indicating a high risk (28–35%) of water-based diseases such as diarrhea and gastroenteritis. All DAMIU studied did not meet the microbiological standards of the Minister of Health Regulation No. 2 of 2023. Poor hygiene-sanitary factors, suboptimal water treatment methods, and unhygienic operator behavior are the main causes of contamination. Increased supervision, routine microbiological examinations, operator training, and disciplined maintenance of equipment, as well as public awareness are needed to choose a certified hygienic and sanitation depot. Keywords : Microbial contamination; risk factors; DAMIU